WORKLOAD FORMATION WITH DEA AND FTE METHOD IN PT. PLN LOCATED AT BANGKA BELITUNG - Lina Gozali; Fransiska Lefta; Kenty Lieanda; Lilyana Lilyana; Tri Sampurno; Siti Rohana (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2022)
Employee composition problem at PT. PLN (Persero) Bangka Belitung Region is still on demand. When a unit needs more employees, the unit makes a request for additional employees. Even though, it is not important to unit needs, moreover the background at additional employees cannot tell to add a number of these employees. The 35,000 MW project increases the number of projects in generation and distribution and transmission. Workload problems are influenced by the number of employees composition in a section, employees’ competency, etc. Workload samples taken from each rayon found that Pangkal Pinang Rayon has the highest workload ratio in PLN Babel, the difference with other rayon is 6915.43 with the number of customers to 145,224 with the total number of employees 21 people. The total composition of employees is measured by Full Time Equivalent and Data Envelopment Analysis method is combined with business data to get the appropriate number of employees so that the reporting of workload data does not burden the employees in their daily activities. Due to a greater workload or lot compared to other offices. Therefore, an increase in workforce is needed.AbstrakMasalah komposisi pegawai di PT PLN (Persero) Wilayah Bangka Belitung masih on demand. Ketika unit membutuhkan lebih banyak karyawan, unit membuat permintaan untuk karyawan tambahan. Padahal, tidak penting untuk kebutuhan unit, apalagi latar belakang di karyawan tambahan tidak bisa menyuruh untuk menambah sejumlah karyawan tersebut. Proyek 35.000 MW meningkatkan jumlah proyek dalam pembangkitan dan distribusi dan transmisi. Masalah beban kerja dipengaruhi oleh jumlah komposisi karyawan dalam suatu bagian, kompetensi karyawan, dll. Sampel beban kerja yang diambil dari setiap rayon menemukan bahwa Pangkal Pinang Rayon memiliki rasio beban kerja tertinggi di PLN Babel, selisihnya dengan rayon lainnya adalah 6915,43 dengan jumlah pelanggan menjadi 145.224 dengan jumlah karyawan 21 orang. Komposisi total karyawan diukur dengan metode Full Time Equivalent dan Data Envelopement Analysis dikombinasikan dengan data bisnis untuk mendapatkan jumlah karyawan yang sesuai sehingga pelaporan data beban kerja tidak membebani karyawan dalam kegiatan sehari-hari mereka. Karena beban kerja atau lot yang lebih besar dibandingkan dengan kantor lain. Oleh karena itu, diperlukan peningkatan tenaga kerja. Kata Kunci: beban kerja; Setara Penuh Waktu; Data Bisnis; Analisis Penyelubungan Data